PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PENIPUAN INVESTASI BODONG SAPI PERAH DI WILAYAH KABUPATEN MUARO JAMBI (STUDI KASUS CV. NUR ASROF SEJAHTERA) - Yoppy Ariansyah; M. Zen Abdullah (Legalitas: Jurnal Hukum, 2021)
The criminal act of fraudulent / imaginary investment fraud continues to increase in both the number and the mode of operation committed by irresponsible parties. The rise of fraudulent investment fraud activities can occur in the midst of people's lives, this has occurred in practice in the Muaro Jambi Regency area, which was carried out by CV. Nur Asrof Sejahtera by marketing investment products for bulking of dairy cows from August 2017 to February 2020, which have claimed quite a lot of victims and the number of losses is quite large. As a result of the fraudulent investment fraudulent acts / crimes that cause material and immaterial losses to the victims. From what is described above, the research objectives are to find out and provide an explanation of the legal protection of victims of criminal investment fraud of dairy cow bulging, To find out and to provide an overview of the problems encountered in legal protection for victims of criminal investment fraud of dairy cow bulging, To find out and provide alternative solutions to problems encountered in legal protection against victims of fraudulent investment in the investment of dairy cattle in Muaro Jambi Regency (case study of CV. Nur Asrof Sejahtera). To answer the above problems, a juridical empirical research method is used as the main / primary material, by describing, analyzing and evaluating all laws and regulations relating to legal protection of victims of invalid and synergized investment. In view of the practice, whether legal protection for victims to obtain compensation in the form of compensation or restitution is a priority to be resolved through merging the compensation case with the criminal case, after the perpetrator is sentenced to imprisonment. The results of the study show legal protection for victims of fraudulent investment fraud of dairy cows in Muaro Jambi Regency, is still neglected and has not been maximally implemented through the merger of the compensation case with the criminal case as is possible in Article 98 paragraph (1) of the Criminal Procedure Code, after the perpetrator is sentenced to imprisonment, the case is considered complete and the victim can only file a lawsuit against the law through a lawsuit. civil and class action. So suggestions It is hoped that there will be courage and empathy for law enforcement officials (court judges), to carry out law enforcement progressively, not only by imposing formal legal justice by convicting perpetrators of criminal acts, but applying substantive justice (protecting the interests / rights of victims) who suffer material and immaterial losses for the said fraudulent act / crime